2016
DOI: 10.1016/j.exppara.2016.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Foetal death in naive heifers inoculated with Neospora caninum isolate Nc-Spain7 at 110 days of pregnancy

Abstract: Neospora caninum infection is a leading cause of abortion in cattle worldwide. The pathogenesis of bovine neosporosis, particularly during the second term of gestation when most abortions occur in naturally infected dams, is poorly understood. In the present study foetal death was observed in 3 of 6 experimentally infected dams at 110 days of gestation after 6 weeks of experimental period. All experimental heifers were febrile between 3 and 5 days post infection (dpi). Inoculated dams seroconverted by 3-4 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 35 publications
9
26
1
Order By: Relevance
“…The biphasic temperature response found in the subcutaneous challenge group (G5) had been previously described after subcutaneous challenge in sheep [ 11 , 28 , 30 ] and cattle [ 33 , 34 ]. Previous studies in cattle have described differences in rectal temperatures between aborting and non-aborting dams [ 19 , 35 ] in the same way as observed in G4 (10 2 , IV) in the present study.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The biphasic temperature response found in the subcutaneous challenge group (G5) had been previously described after subcutaneous challenge in sheep [ 11 , 28 , 30 ] and cattle [ 33 , 34 ]. Previous studies in cattle have described differences in rectal temperatures between aborting and non-aborting dams [ 19 , 35 ] in the same way as observed in G4 (10 2 , IV) in the present study.…”
Section: Discussionsupporting
confidence: 84%
“…With regard to clinical observations, foetal viability is the most significant parameter to be evaluated in an abortion model of neosporosis [ 14 ]. Infection of cattle at mid-term gestation with 10 7 tachyzoites of the Nc-Spain7 isolate caused foetal death in 50% of infected animals after an experimental period of 6 weeks [ 19 ]. All pregnant ewes intravenously infected with 10 5 tachyzoites (G1) aborted in the same way as pregnant ewes intravenously infected with a 10-fold higher dose (10 6 tachyzoites) [ 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences may be explained by their biological diversity, as has been demonstrated in previous in vivo studies [ 16 , 18 , 20 , 29 , 32 , 51 , 52 ]. Nc-Spain7 showed a high neonatal mortality (95%) and vertical transmission rate (nearly 80%) in a pregnant BALB/c mouse model [ 31 ], as well as a percentage of abortion and vertical transmission as high as 100% in a bovine model [ 20 , 53 ]. However, Nc-Spain1H showed a 100% offspring survival rate and a low vertical transmission rate (5%) in a pregnant mouse model [ 29 ], and no foetal death was observed in experimentally infected cattle [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limiting of histopathology is the subjective criterion because need an expert evaluator, in contrast to PCR and ELISA that are objectives diagnostic test (ORTEGA-MORA et al, 2006). ELISA need a high level of antibodies to detect a positive sample; considering immunology system of fetus recollected is in developing, titers of antibodies may not reach cut-off ELISA, need more time to produces more immunoglubuline or the parasite burden was low (ALMERÍA et al, 2016;PEREIRA-BUENO et al, 2003) PCR diagnostic performance is very high, detecting presence of small amounts of N. caninum DNA in large quantity of sample; moreover, PCR detect DNA in tissues of autolysed fetuses (VAN MAANEN et al, 2004). In conclusion, PCR in our study demonstrated be more sensitivity than ELISA in aborted fetus samples.…”
Section: Discussionmentioning
confidence: 99%